Designing Climate Policy: Lessons from the Renewable Fuel Standard and the Blend Wall. (11th January 2018) - Lade, Gabriel E; Cynthia Lin Lawell, C‐Y; Smith, Aaron
Abstract: Many policies mandate renewable energy production to combat global climate change. These policies often differ significantly from first‐best policy prescriptions. Among the largest renewable energy mandates enacted to date is the Renewable Fuel Standard (RFS), which mandates biofuel consumption far beyond what is feasible with current technology and infrastructure. We critically review the methods used by the Environmental Protection Agency to project near‐ and long‐term compliance costs under the RFS, and draw lessons from the RFS experience to date that would improve the program's efficiency. The lessons are meant to inform both future RFS rulemaking and the design of future climate policies. We draw two lessons specific to the RFS. First, incorporate uncertainty into rulemaking; second, implement multi‐year rules. Multi‐year rulemaking allows for longer periods between major regulatory decisions and sends greater certainty to markets. We also provide two more general recommendations: tie waiver authority to compliance costs or include cost containment provisions, and fund research and development of new technologies directly rather than mandating them. Future technological advancement is uncertain, and mandating new technologies has proven to be largely ineffective to date, particularly in fuel markets.